American Economic Hardship in Go Down Moses by William Faulkner - Ichsan, Muhammad Fiqri (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2022)
This research investigates the representation of rural life in America in Go Down Moses by William Faulkner, especially in their economic mindset because most of the people in the village have a unique mindset that they have to move to the big city to get more successful. This analysis would like to give a new perspective on this mindset that people in the village can utilize the land in their village to get more money to get more successful they do not need to move to the bigger city for they can use their land by husbandry, agriculture, and fishery. The research used American Pastoral theory and the theory of ecocriticism. Go Down Moses is a novel with seven different stories, and each story with a different conflict in each story and the investigation will focus on the background and setting of the Environment in the story. And it will give the reader a new insight into utilizing land, especially in the village. This research is important to invite people awareness of utilizing the land for their living and throw away the wrong mindset that we have to move to the big city to get a better life.